2020
DOI: 10.1016/j.ejvs.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Patient Specific Flow Predictions to Improve Haemodialysis Arteriovenous Fistula Maturation (Shunt Simulation Study): A Randomised Controlled Trial

Abstract: WHAT THIS PAPER ADDS Arteriovenous fistula (AVF) maturation remains a permanent issue in vascular access surgery for haemodialysis treatment. Numerous studies have tried to improve clinical decision making or predict maturation probability. The present study shows that a new and innovative patient specific computation model accurately calculates postoperative access flows, and as flow is related to maturation, this model may potentially improve AVF maturation rates.Objective: An arteriovenous fistula (AVF) nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Finally, as for the AVF non-maturation, the obtained confusion matrix confirmed the high accuracy of the predictions, equal to 96.8%, significantly higher than the NIR. Our tool also allows to easily evaluate the impact of VA characteristics on maturation, BFVs and diameters, as in other works, 21 thanks to the inclusion of predictor type, which summarizes AVF location and configuration. When a new patient is analyzed, the output variables can be predicted considering their characteristics and the different alternatives for VA type.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as for the AVF non-maturation, the obtained confusion matrix confirmed the high accuracy of the predictions, equal to 96.8%, significantly higher than the NIR. Our tool also allows to easily evaluate the impact of VA characteristics on maturation, BFVs and diameters, as in other works, 21 thanks to the inclusion of predictor type, which summarizes AVF location and configuration. When a new patient is analyzed, the output variables can be predicted considering their characteristics and the different alternatives for VA type.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not allow to preoperatively predict BFV in the AVF at maturation. Zonnebeld et al 24 recently reported the results of the Shunt Simulation Study, the clinical validation of a computational model able to predict the immediately postoperative AVF flow starting from preoperative data. As shown by the authors, the model performance was satisfactory, but its use did not improve AVF maturation in the simulation group as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models for AV access have been proposed in several studies before. [5][6][7] One of the most notable studies is the 'Shunt Simulation Study', where the authors aimed to validate a prediction model for AV maturation based on preoperatively calculated flow simulations. Unfortunately, the study did not validate the desired outcome, which was an increased number of matured AVFs.…”
Section: Discussionmentioning
confidence: 99%